Short-Season Corn Cost-Return Budget in Southeast Kansas - Fogleman, Sarah L. (My University, 2000)
This publication outlines the expected costs and returns for short-season corn in southeast Kansas.
MF993_2000_10
Keywords: MF993; Economics; Crops; MF